IMPLEMENTATION OF SKINNER’S OPERANT CONDITIONING THEORY IN THE LEARNING PROCESS IN CLASS V OF MUHAMMADIYAH BIAK PRIMARY SCHOOL - Hanani Qurrata Ayun; Marwan Sileuw; Didik Efendi (Waniambey: Journal of Islamic Education, 2025)
This study examines the application of Burrhus Frederic Skinner’s Operant Conditioning theory in shaping the personalities of students in Grade V of Muhammadiyah Biak Elementary School. This theory emphasises the importance of positive and negative reinforcement to encourage desired behaviour, but its application in this school is still intuitive and inconsistent. Positive reinforcement through verbal praise has proven effective in increasing student participation, although some students prefer concrete reinforcement such as stickers or physical rewards. Negative reinforcement, such as exemption from tasks, is rarely applied systematically, while positive punishment through verbal reprimands is often ineffective, especially for sensitive students. This study found that the formation of student discipline and responsibility is beginning to be seen, but its effectiveness is hampered by the lack of a consistent and structured reinforcement system. Therefore, further efforts are needed to create a more structured, consistent, and tailored reward and punishment system to strengthen the formation of desired behaviour in the long term.